Towards a Multi-theoretical Approach on the Board and Firm Performance Relationship - Tien, Nguyen Thu Thuy (H. : ĐHQGHN, 2020)
Recent reviews of research on company boards and firm performance relationship tend to criticise three of the main traditional theories on boards, namely Agency Theory (AT), Resource Dependence Theory (RDT), and Managerial Power Theory (MPT) for their narrow assumptions and focuses on a limited range of board tasks. This study provides a critical review on these above theories and promotes a direction towards an integrated approach with three important governance factors, namely board capability, board incentives, and CEO power for a better understanding of board-firm performance relationship.